2013
DOI: 10.3791/50512
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assay to Study Protein:DNA Interactions, Discover Transcriptional Regulators of Gene Expression, and Identify Novel Anti-tumor Agents

Abstract: Many DNA-binding assays such as electrophoretic mobility shift assays (EMSA), chemiluminescent assays, chromatin immunoprecipitation (ChIP)-based assays, and multiwell-based assays are used to measure transcription factor activity. However, these assays are nonquantitative, lack specificity, may involve the use of radiolabeled oligonucleotides, and may not be adaptable for the screening of inhibitors of DNA binding. On the other hand, using a quantitative DNA-binding enzyme-linked immunosorbent assay (D-ELISA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Additionally, certain transcription factors, such as eukaryotic nuclear receptors ( 39 ), do not tightly bind to the target DNA sequences in the absence of a ligand. PDI-ELISA could be a great tool to screen and identify small molecule ligands that enable the transcription factor binding to the target DNA sequence ( 40 ) (Figure 6B ). Furthermore, small molecule or protein activators may induce DNA conformational change and therefore greatly enhance the DNA binding of a DNA-binding protein to the target DNA sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, certain transcription factors, such as eukaryotic nuclear receptors ( 39 ), do not tightly bind to the target DNA sequences in the absence of a ligand. PDI-ELISA could be a great tool to screen and identify small molecule ligands that enable the transcription factor binding to the target DNA sequence ( 40 ) (Figure 6B ). Furthermore, small molecule or protein activators may induce DNA conformational change and therefore greatly enhance the DNA binding of a DNA-binding protein to the target DNA sequence.…”
Section: Resultsmentioning
confidence: 99%
“…A critical Met residue within the Runt domain also mediates association with its essential cofactor Cbfβ, which increases DNA binding 10-fold relative to Runt alone (Tahirov et al, 2001). Using a quantitative DNA-binding assay (D-ELISA) specific for RUNX2 (Underwood et al, 2012; Underwood et al, 2013), we showed that RUNX2 with a Cys mutation in the Runt domain (Cys118Ser) did not bind DNA (Underwood et al, 2012). Furthermore, a GFP-tagged Runt domain vector mutated at position Met-143 of the Runt domain (which inhibits Cbfβ binding) exhibited reduced DNA binding relative to wild type Runt domain (Underwood et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As a first step to determine, which of the five ACGT motifs function as XBP1s and/or 228 ATF6(N) binding sites for promoter activation, we measured the binding of these TFs to 229 portions of the MIEP by using a DNA-protein interaction ELISA (DPI-ELISA, (Brand et al, 230 2010;Underwood et al, 2013). Microtiter plates were coated with double-stranded 231 oligonucleotides encoding three copies (27 nucleotides each) of a putative binding motif with 232 adjacent sequences on either side (Table S3) XBP1s, XBP1u, or ATF6(N) (Fig.…”
Section: Xbp1 -/-mentioning
confidence: 99%
“…The DPI-ELISA was performed essentially as described in detail elsewhere (Brand et al, 415 2010;Underwood et al, 2013). Terminally biotinylated dsDNA oligonucleotides containing 3 416 copies of putative TF binding sites (Table S3) were purchased from Eurofins.…”
Section: Immunoblot Analysis 367mentioning
confidence: 99%